Exploring the Role of Theory of Mind in Moral Judgment: The Case of Children with Autism Spectrum Disorder - Fadda, Roberta; Parisi, Marinella; Ferretti, Luca; Saba, Gessica; Foscoliano, Maria; Salvago, Azzurra; Doneddu, Giuseppe (Frontiers in Psychology, 2016)
This paper adds to the growing research on moral judgment by considering whether Theory of Mind (ToM) might foster children's autonomous moral judgment achievement. A group of 30 children with Autism Spectrum Disorder (ASD) was compared in moral judgment (MJ) and ToM with 30 typically developing (TD) children. Participants were tested for moral judgment with a classical Piaget’s task and for ToM with a second order False Belief task. In the moral task, children were told two versions of a story: in one version the protagonist acted according to a moral intention but the action resulted in a harmful consequence; in the other version the protagonist acted according to an immoral intention, but the action resulted in a harmless consequence. Children were asked which of the two protagonists was the “naughtier”. In line with previous studies, the results indicated that, while the majority of TD participants succeeded in the second order False Belief task, only few individuals with ASD showed intact perspective taking abilities. The analysis of the MJ in relation to ToM showed that children with ASD lacking ToM abilities judged guilty the protagonists of the two versions of the story in the moral task because both of them violated a moral rule or because they considered the consequences of the actions, ignoring any psychological information. These results indicate a heteronomous morality in individuals with ASD, based on the respect of learned moral rules and outcomes rather than others’ subjective states.